Increasing the role of zakat institutions in poverty reduction through productive zakat programs in Indonesia - Haron, Razali; Sutrisno, Sutrisno (2019)
Zakat Institutions have an essential role in helping the poor and the zakat recipient through empowerment programmes. Thus, zakat has a significant contribution to Muslims’ life, especially in alleviating poverty. Furthermore, zakat institutions as mediators between rich people and poor people with various programs to reduce poverty. However, even though the allocation of zakat funds has been improved and is growing every year, the problem of poverty, unemployment, and inequality has caused many issues to be debated. This study intends to discuss poverty alleviation programs made by zakat institutions in Indonesia through productive zakat programs by using descriptive qualitative methods. Managed and distribution of zakat funds with a productive zakat programmes are reviewed and provided as model of zakat distribution. Finding of implementing productive zakat on the zakat institution in Indonesia are presented. While provisional solution are recommended with a hope of contributing better solutions. At the end of discussion, a list recommendations for future researches is suggested for consideration.